PENERAPAN SIMBOL OPERASI MATEMATIKA SEDERHANA SEBAGAI DASAR MENGHILANGKAN ESSENSI BUNGA BANK DALAM PERSPEKTIF ISLAM - Tri Wahyu Budiutomo (Intersections, 2021)
According to Islam, bank interest on credit activities is included in the category of "usury" which is forbidden for Islam. The problem of bank credit activities is a very important need for people in doing business. The purpose of this paper is to try to use simple mathematical symbols to try to eliminate the essence of usury. Changing the essence of "usury" with the concept of cooperation and using a simple symbol "=" can eliminate the essence of usury, of course everything must be based on good intentions and honesty